Digital technology in the early years: A reflection of the literature - Teichert, Laura; Salman, Munizah (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2021)
Early childhood education is rooted in developmentally appropriate practice and play-based learning curricula. In the 21st century, practitioners experience tensions when they are unsure of how to navigate digital childhoods while being confronted with contradictory information. For instance, early learning frameworks recognize the need for children to develop digital literacy skills, yet pediatric societies recommend limiting screen time. Thus, practitioners are left without best practice guidelines that would help them embed technology into early learning environments through pedagogies that align with play-based learning. This review examines research to date on age-appropriate and playbased uses of digital technology that could more naturally fit in preschool and kindergarten classrooms while also highlighting the potential benefits of using tablets in early learning classrooms.